Social Cognitive Theory (SCT) Based Breastfeeding Education Model: Implications for Early Breastfeeding Practices and Maternal Self-Efficacy in Badung Regency, Bali - Putu Ayu Dina Saraswati Dina Saraswati; Ni Putu Yunita Sri Lestari; I Wayan Adi Artha Wiguna; Babucarr Jassey (Universitas Nahdlatul Ulama Surabaya, 2026)
Exclusive breastfeeding coverage in Indonesia, including Badung District, remains below the national target of 67%. Maternal self-efficacy and employment status are key barriers, often leading to early introduction of formula feeding. This study aimed to analyze the effect of a breastfeeding education model based on Social Cognitive Theory (SCT) on early breastfeeding practices, maternal self-efficacy, and infant growth. A quasi-experimental study with a non-equivalent control group design was conducted involving 76 postpartum mothers (38 in the intervention group and 38 in the control group), recruited on the third day postpartum. The intervention group received SCT- based breastfeeding education for six weeks, while the control group received standard breastfeeding education. Data were analyzed using Chi-square, Mann–Whitney, and t- tests, with a significance level set at p < 0.05. The intervention group demonstrated significantly higher post-test scores for early breastfeeding practices (36.16 vs. 29.37; p < 0.001) and maternal self-efficacy (52.00 vs. 38.71; p < 0.001) compared with the control group. SCT-based breastfeeding education is effective in improving early breastfeeding practices and enhancing maternal self-efficacy. Its integration into breastfeeding promotion programs is recommended to optimize maternal and child health outcomes.